Transcendental Politics from the Perspective of Transcendental Theosophy - Ayatullah Jawadi amuli (حکمت اسرا, 2011)
Transcendental politics is a politics that is global and all-encompassing. It considers man as sublime life as opposed to a rational animal. According to Transcendental Theosophy, man creates his own world and afterlife which is regimented based on transcendental politics. This article analyzes and presents the sources and compositions of transcendental politics from the perspective of Transcendental Theosophy.